2009
DOI: 10.1186/1471-2199-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Validation of suitable house keeping genes for hypoxia-cultured human chondrocytes

Abstract: Background: Hypoxic culturing of chondrocytes is gaining increasing interest in cartilage research. Culturing of chondrocytes under low oxygen tension has shown several advantages, among them increased synthesis of extracellular matrix and increased redifferentiation of dedifferentiated chondrocytes. Quantitative gene expression analyses such as quantitative real-time PCR (qRT-PCR) are powerful tools in the investigation of underlying mechanisms of cell behavior and are used routinely for differentiation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 42 publications
8
81
0
Order By: Relevance
“…However, for C. batrachus, ACTB and B2M, widely used RG internal controls (Lupberger et al 2002) were the least stable genes identified by all three analysis methods in examined tissues under normoxic and/or hypoxic conditions. These results were consistent with the earlier reports, which found ACTB to be highly regulated by treatments and have unstable expression in hypoxia-cultured human chondrocytes and lipopolysaccharide-stimulated human THP-1 and K562 cells (Cao et al 2012;Foldager et al 2009), whereas B2M was the least stable gene in human reticulocytes (Silver et al 2006). The present study on C. batrachus revealed novel candidate RGs (RPL30, TUB, 28S rRNA and ELF-1A) with a more stable expression in experimental contexts, in comparison to frequently used RGs (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…However, for C. batrachus, ACTB and B2M, widely used RG internal controls (Lupberger et al 2002) were the least stable genes identified by all three analysis methods in examined tissues under normoxic and/or hypoxic conditions. These results were consistent with the earlier reports, which found ACTB to be highly regulated by treatments and have unstable expression in hypoxia-cultured human chondrocytes and lipopolysaccharide-stimulated human THP-1 and K562 cells (Cao et al 2012;Foldager et al 2009), whereas B2M was the least stable gene in human reticulocytes (Silver et al 2006). The present study on C. batrachus revealed novel candidate RGs (RPL30, TUB, 28S rRNA and ELF-1A) with a more stable expression in experimental contexts, in comparison to frequently used RGs (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, Foldager et al found that TBP was the RG with the highest expression stability in 3D cultivated human chondrocytes. 29 In a study on human adipose-derived stem cells during hypoxic culture, osteogenic and chondrogenic differentiation, Fink et al identified TBP being among the most stable RGs. 28 The present data are in line with an earlier study of Kulkarni et al, in which TBP and HPRT1 were determined to be the most stable RGs in human cornea (46).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Commonly used RGs, for example, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and beta actin (ACTB), were observed to be less stable or regulated under certain culture conditions in MSCs, chondrocytes, and fibroblasts. [27][28][29][30] We recently showed that the combined use of DNA-damageinducible alpha (GADD45A), pumilio homolog 1 (PUM1), and large ribosomal protein P0 (RPLP0) significantly improved gene expression accuracy compared with classically used RGs, ACTB, and GAPDH in 2D osteogenically stimulated bone marrow-derived MSCs (BM-MSCs). 31 Numerous putative RGs have been reported for a wide variety of human cell lines and primary cells under different experimental conditions, almost exclusively under standardized 2D cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the level of contamination of the skin swab material by human DNA, we performed qPCR for a human housekeeping gene (GAPDH) which is present in all nucleated cells of human origin (10). The GAPDH qPCR was performed in parallel with the bacterial qPCRs.…”
Section: Validation Of Taqman Mgb Probesmentioning
confidence: 99%